Relationship between static natural head position and head position measured during walking - (:unkn) unknown (MOSBY, INC, 2006)
Introduction: The aim of this project was to determine whether there is a statistically significant difference between the means of static and dynamic (measured during walking) measurements of head posture. Methods: The sample consisted of 50 subjects, 25 women and 25 men, 20 to 25 years of age. None had a history of orthodontic treatment, head or neck injury, or nasal breathing problems, and none wore eyeglasses to correct vision. Static measurement of head position was recorded by using the self-balance position. Dynamic measurements of head position were, made with an inclinometer device with the subject walking in a relaxed manner for 5 minutes. The data, measured in degrees, were stored in a pocket data logger. Recorded static and dynamic head posture data were transferred to a computer for analysis. The means of the measurements were statistically compared with the t test (alpha = .05). The mean walking head position was tipped forward relative to the mean static head position. Results: The mean value of static position minus walking head position measurements was +4.60 degrees. The differences between the 2 recordings were statistically significant (P < .001). Conclusions: Static and walking head position measurements are not interchangeable. Therefore, it might be advisable to use the mean dynamic measurement of head position to represent natural head position for positioning when taking case records such as lateral and posteroanterior cephalograms, clinical extraoral photography, or 3-dimensional imaging.
Keywords: CRANIOFACIAL MORPHOLOGY; DYNAMIC MEASUREMENT; POSTURE; CEPHALOMETRICS; INCLINOMETER